Pengaruh Metode Demonstrasi Pada Pembelajaran Pendidikan Agama Islam Terhadap Minat Belajar Siswa - Yulia, Putri; Penta Putra, Dendi (Malewa: Journal of Multidisciplinary Educational Research, 2024)
This research is motivated by the phenomenon, namely the low interest in learning of students in learning Islamic religious education. This research aims to determine the effect of the demonstration method in Islamic religious education learning on students' interest in learning. This research method is a quantitative quasi experiment, with a nonequivalent control group design. The population in this study were 95 class IX students. This research used 2 classes, namely the experimental class using the demonstration method and the control class using commonly used methods such as the lecture method. Data on student learning interest was obtained through a scale with a Likert scale model. The data analysis technique uses the t test formula with the help of the SPSS application. The calculation used is a comparative analysis of the posttest scores of the control class and the experimental class. The results of this statistical analysis showed that the significance (2-tailed) was 0.000 < 0.05. So, it can be concluded that the results of this research reveal that there is an influence of the demonstration method on students' interest in learning, because learning using the demonstration method can increase students' interest in learning.